دراسة لبعض المكونات الكيماويو للأجزاء الخضرية في نباتي السدر Cordia L. والبنبر Ziziphus spina-christi L. Wild.var. spina-christi myxa: The Study of Some Chemical Components of Vegetative Parts of Jujube Ziziphus spina-christi L. Wild.var. spina-christi And Banber Cordia myxa L. Plants - صكَر ر ا زق عبد المحسن (University of Thi-Qar Journal of Science, 2014)
A study was carried out during the mansoon 2006-2007 at Al-Nassiriyia province, Thi-Qar governorate toestimation the chemical component of the vegetative parts for Jujube Ziziphus spina-christi L. Wild.Var. spinachristi and Banber Cordia myxa L. plants.The Results can summarized as following :- Young leaves of Banber were giving the high percentages of water content (84.415%) whereas fruit ranches of Jujube which was one year aged giving the low percentage (42.600%).Dry matter content in fruit ranches of Jujube which was one year aged were giving the high percent (57.400%) but the younger leaves of anber were giving the low percent (15.585%).Total ash on the both mature leaves of Banber and Jujube produced the high percent (4.289%) but the low percentage found in the younger leaves of Banber and fruit branches of Jujube which was less than one year age. Whereas the high percentages of Phenols (Tannins) were ported in the fruit branches of Jujube which was less than one year aged (14.177%),and the low percentages were found in the fruit branches of Banber which was one year aged and youngerleaves of both plants. Total roteins in younger leaves of Jujube were the highest (16.043%) and the low percentageswere found in the fruit branches of Banber which was one year aged (6.043%).The highest value of total Saponins was found in the younger leaves of Banber (7300.000 μg/100gm dry weight) but the low percentages(2933.330μg/100gm dry weight) were found in the mature leaves of Jujube.